Endosomal sorting and c-Cbl targeting of paxillin to autophagosomes regulate cell-matrix adhesion turnover in human breast cancer cells - Chang, Chia-Hao (Oncotarget, 2017)
Post-translational mechanisms regulating cell-matrix adhesion turnover during cell locomotion are not fully elucidated. In this study, we uncovered an essential role of Y118 site-specific tyrosine phosphorylation of paxillin, an adapter protein of focal adhesion complexes, in paxillin recruitment to autophagosomes to trigger turnover of peripheral focal adhesions in human breast cancer cells. We demonstrate that the Rab-7 GTPase is a key upstream regulator of late endosomal sorting of tyrosine118-phosphorylated paxillin, which is subsequently recruited to autophagosomes via the cargo receptor c-Cbl. Essentially, this recruitment involves a direct and selective interaction between Y118-phospho-paxillin, c-Cbl, and LC3 and is independent from c-Cbl E3 ubiquitin ligase activity. Interference with the Rab7-paxillin-autophagy regulatory network using genetic and pharmacological approaches greatly impacted focal adhesion stability, cell locomotion and progression to metastasis using a panel of human breast cancer cells. Together, these results provide novel insights into the requirement of phospho-site specific post-translational mechanism of paxillin for autophagy targeting to regulate cell-matrix adhesion turnover and cell locomotion in breast cancer cells.